Factors influencing the public's intention to contribute in health waqf - Abd Aziz, Nurul Aien; Sapuan, Noraina Mazuin; Muhamad Tamyez, Puteri Fadzline (Universiti Teknologi MARA, Cawangan Johor, 2023)
The health sector is crucial as it supports the population in maintaining good health. To ensure sustainability in the future, the health sector needs to be supported by adequate financial resources. To cater to the needs of the underprivileged and those in need, health waqf is seen as a potential instrument to assist the government in channelling community contributions to finance the escalating medical costs each year. Therefore, this study aims to investigate the relationship between attitude, subjective norm, perceived behavior control, level of understanding, financial and the public's intention to contribute in health waqf. A total of 137 respondents from the public in Johor and Melaka participated in this survey. Convenience sampling was used to measure attitude, subjective norm, perceived behavior control, level of understanding, financial and the public's intention to contribute in health waqf. Pearson correlation was used to assess the relationships between variables. Furthermore, the findings also revealed that only two variables which are attitude and financial has a significant influence on the public's intention to contribute in health waqf. Lastly, the findings from this study will be beneficial to the State Islamic Religious Council (SRIC), Department of Awqaf, Zakat and Hajj (JAWHAR), relevant ministries, and policymakers in improving this health waqf instrument in the future.